2020
DOI: 10.1186/s12879-020-05218-w
|View full text |Cite
|
Sign up to set email alerts
|

Conidiobolus pachyzygosporus invasive pulmonary infection in a patient with acute myeloid leukemia: case report and review of the literature

Abstract: Background Conidiobolus spp. (mainly C. coronatus ) are the causal agents of rhino-facial conidiobolomycosis, a limited soft tissue infection, which is essentially observed in immunocompetent individuals from tropical areas. Rare cases of invasive conidiobolomycosis due to C. coronatus or other species ( C.incongruus, C.lamprauges ) have been reported in immunocompromised patients. We report here the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Previous studies have mostly studied the relationship between sTREM-1 and PCT levels and pulmonary fungal infection and found that their levels can reflect the degree of pulmonary fungal infection [19,20]. A large number of studies have also confirmed that the serum level of 1,3-β-D It was reported that the levels of 1,3-β-D and sTREM-1 in the plasma of patients with pulmonary fungal infection increased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have mostly studied the relationship between sTREM-1 and PCT levels and pulmonary fungal infection and found that their levels can reflect the degree of pulmonary fungal infection [19,20]. A large number of studies have also confirmed that the serum level of 1,3-β-D It was reported that the levels of 1,3-β-D and sTREM-1 in the plasma of patients with pulmonary fungal infection increased.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have mostly studied the relationship between sTREM-1 and PCT levels and pulmonary fungal infection and found that their levels can reflect the degree of pulmonary fungal infection [ 19 , 20 ]. A large number of studies have also confirmed that the serum level of 1,3- β -D glucan in patients with pulmonary fungal infection is increased, and the increase in the serum level of 1,3- β -D glucan in patients with fungal infection is more obvious than that in patients with bacterial infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, PSZ tablets, which are widely used and unlikely to result in underexposure, may not justify routine TDM. 168,169,234,235,236,[238][239][240][241][244][245][246] Blood Trough 261,262,268,[281][282][283][284]314,315,320,323,327,330,331,333,340 Concentrations Targets 341,344,347,350,352,353,355,[358][359][360][361] and TDM Indications 364,522,[526][527][528][529][530][531][532][533][534][535][536]…”
Section: Discussionmentioning
confidence: 99%
“…AF TDM cases in real-life settings (pathogens, underlying diseases, 69,71–73,75,81 trends per year, 84,234,235,236,238,239,241,244,245,344–348 CNS 532–539 localization 541–566 ) 364,370,499,522,527–530 Trends are concerning a majority of mucomycosis and aspergillosis, in oncohematology and transplantation. VRZ, more recently PSZ tablets and ISZ are the most represented.…”
Section: Tdm For Af Drugsmentioning
confidence: 99%
See 1 more Smart Citation